The Effect of Substrate Concentration on Enzymatic Hydrolysis of Selected Food Waste for Glucose Production (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Glucose is an important commodity for various domestic and industrial applications, rangingfrom the manufacturing of food and pharmaceuticals to biofuel production. It is thereforeimperative to explore novel sources of glucose that are easy to process, cheap andenvironmentally friendly. In this study, food wastes collected from restaurants and cafeteriawithin Universiti Malaysia Sarawak (UNIMAS) campus were used as feedstock for glucoseproduction. Several feedstock loadings were investigated (7%, 10%, 20% and 30% w/v) in theenzymatic hydrolysis processes that were carried out at pH 5.0, 100 rpm and 58 Â± 2 Â°C for 24 husing glucoamylase and crude protease preparations. Results showed that substrateconcentration of 20% (w/v) in batch hydrolysis experiments has the highest glucose productionat 140 g/L, with 46.20% glucose recovery. The highest amount of substrate being hydrolyzed(68.35%) within 20 h was also recorded in the same experimental set. We conclude thatsubstrate concentration or feedstock loading during enzymatic hydrolysis is a very crucialparameter for optimal glucose production and recovery from carbohydrate rich food wastes.
Keywords: Glucose, Food waste Substrate concentration, Enzymatic hydrolysis, Glucose recovery